Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.indcrop.2019.04.064
|View full text |Cite
|
Sign up to set email alerts
|

The possibility for improvement of flowering, corm properties, bioactive compounds, and antioxidant activity in saffron (Crocus sativus L.) by different nutritional regimes

Abstract: Saffron as one of the most precious spices and medicinal plants, is highly valued for its bioactive compounds. Quantity and quality in spices and medicinal plants can be improved by the plant nutrition. In this field study the sole and integrated application of various fertilizers types and arbuscular-mycorrhizal fungus (AM), Glomus mosseae with respect to the flower-related traits, corm properties, quality, bioactive compounds and antioxidant activity of saffron at Kerman region, Iran was examined over a thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 48 publications
6
30
1
Order By: Relevance
“…Vermicompost fertilizer is suitable for the long growth season of the Moringa oleifera tree, with its low rate of nutrients degradation speed [44,60]. The results of the present study agree with those of other studies that have shown that increased vermicompost consumption improved vegetative features, while it also improved dry matter content and flowering [47,48,[61][62][63][64][65][66][67] along with fruiting, seeds, and oil yield. These findings agree with those of Arancon et al [68], Arancon et al [44], Atiyeh et al [69], Liuc and Pank [70] and Muscolo et al [71] who found that using vermicompost improved growth and flowering parameters as well as quantitative and qualitative parameters of strawberry, petunia, marigold and roman chamomile, and wild carrot.…”
Section: Effects Of Vermicompostsupporting
confidence: 87%
“…Vermicompost fertilizer is suitable for the long growth season of the Moringa oleifera tree, with its low rate of nutrients degradation speed [44,60]. The results of the present study agree with those of other studies that have shown that increased vermicompost consumption improved vegetative features, while it also improved dry matter content and flowering [47,48,[61][62][63][64][65][66][67] along with fruiting, seeds, and oil yield. These findings agree with those of Arancon et al [68], Arancon et al [44], Atiyeh et al [69], Liuc and Pank [70] and Muscolo et al [71] who found that using vermicompost improved growth and flowering parameters as well as quantitative and qualitative parameters of strawberry, petunia, marigold and roman chamomile, and wild carrot.…”
Section: Effects Of Vermicompostsupporting
confidence: 87%
“…Saffron yield is a parameter which depends on many factors as agronomic aspects (density planting, fertilization, irrigation, weed control) [46,47], climatic aspects (air temperature and precipitations), and cultivation site conditions [8,44]. Among soil properties, the texture is the major factor stimulating saffron production [48], because controls the movement and availability of air, nutrients and water [49].…”
Section: Flowering and Quantitative Traitsmentioning
confidence: 99%
“…Daughter corm production is an important part of the gladioli propagation; our study results clearly indicate foliar fertilization has an important role in this sequence of the cultivation. Previous reports have also shown an increase in daughter corms production under foliar fertilization treatments [ 16 , 36 , 37 , 38 ]. Under our experimental conditions the highest increase was recorded in ‘Frizzled Coral Lace’ compared to the other four Gladiolus varieties .…”
Section: Discussionmentioning
confidence: 67%